Observed Urban Heat Island Characteristics in Enugu Urban During the Dry Season (Global Journal of Human-Social Science, 2012)
Aim : The dry season microclimate variation at several sites in Enugu was assessed with the sole aim of determining the UHI characteristics during dry season periods. Study Design: The study design employed in the study was survey design. Place and Duration of the study: Enugu urban was the study area and the study occurred between the months of Feb – Mar 2006 and 2007. Methodology : During the study, transect and fixed point measurements were taken hourly and averaged over a month. All temperature difference was calculated as site temperature minus reference temperature. Thus, a negative (-) temperature difference indicates that the site was cooler than the reference station. The reference station is the rural environment. Results : Dry season months showed strong variability in temperature. The downtown site was the warmest (2.0 0c) during the day. The heavily vegetated urban residential site (LVR) and suburban site (LOR) with fully developed vegetation canopy were the coolest (-3.8 and -2.68).
Keywords: Urban heat island; rural; intraurban